PENERAPAN PEMROGRAMAN DAN PENGANGGARAN SEBAGAI PENUNJANG KEBERHASILAN BERWIRASWASTA - -, Rispantyo (Universitas Slamet Riyadi, 2009)
ABSTRACT Entrepreneur is a pre-eminent personality which express august kindness and nature of proper is byword, because on the basis of ability alone can bear a masterpiece contribution to move forward human which is have truth base to and kindliness. Efficacy of entrepreneur influenced by some factor. One of the factors is skill in applying system operation of management, specially budgeting and program. Program formulated into budget. Afterwards all executors will execute program as according to budget which have been specified. To ascertain budget executed properly, needed by reporting system, conducive doing of difference analysis. Difference can represent beneficial difference, and or difference harming. Thereby corrective action will immediately can be done by if needed, before happened undesirable situation. Keywords: entrepreneur, program, budgeting, difference analysis